Das Händel-Lexikon - Marx, Hans Joachim 1935-; Gervink, Manuel; Voss, Steffen (Laaber Laaber, 2011)
A universal reference work in which you can find answers to virtually all questions relating to George Frideric Handel. 772 keywords provide extremely informative and easy-to-understand information about the most important aspects of Handel's life and work: compositions, genres, instruments, performers, researchers, imitators, librettists, performance venues and places of residence, and much more. (Translated with DeepL.com)
Keywords: Handel, George Frideric -- 1685-1759; 18th Century (1701-1800); Composer; Encyclopedia